End-of-Life Educational Seminar in a Prelicensure Bachelor of Science in Nursing Program. - Jackson, Molly J.; Motley, Cindy L. (Journal of Hospice & Palliative Nursing, 2014)
Nurses today are caring for patients with higher acuity in acute in patient settings and subsequently experience more patient deaths. Since 2011, prelicensure baccalaureate students in their final semester at a nursing school in Northeast Ohio have been required to participate in a half-day end -of-life care seminar modeled after the End-of-Life Nursing Education Consortium program. This seminar incorporates content on symptom management, communication , final hours of life, care of the patient and family experiencing loss, and self-care. This article describes the teaching methods and seminar content and reports the student evaluations and reflective comments. Student evaluations and reflections were very positive. Participants identified learning the most about communication skills, holistic care, and knowing what to expect in the final hours o f life.